Yielding Behavior and Strengthening Mechanisms of a High Strength Ultrafine‐Grained Cr–Mn–Ni–N Stainless Steel. Issue 5 (17th November 2021) - Su, Guanqiao; Xie, Haibo; Huo, Mingshuai; Jia, Fanghui; Wu, Hui; Li, Zhou; Bi, Hongyun; Chang, E.; Xu, Haigang; Jiang, Zhengyi
Abstract : The microstructure of Cr–Mn–Ni–N stainless steel is regulated by a combination of cold deformation and subsequent martensite reversed annealing. The yield strength and tensile strength of the tested steel are greatly improved to 1220 and 1357 MPa, respectively, by conventional heavy cold rolling (66% thickness reduction) and a subsequent annealing process (750 °C for 5 min) relative to those before cold rolling (austenized state); at the same time, the total elongation keeps an appropriate value. The results show that the grain refinement strengthening acts as the primary factor for the strengthening of the tested steels while the precipitation behavior from the M23 C6 ‐type carbides is not quite effective. Additionally, different yield phenomena and microstructural evolution for tested steels with 66% thickness reduction annealed at 750 °C with different holding times are systematically analyzed and discussed. Lüders‐like deformation features noticeably appear but become weakening with the longer annealing time. The change in initial free mobile dislocation density is the core cause of the preyield plateau phenomenon. Abstract : The comprehensive mechanical properties of Cr–Mn–Ni–N stainless steel are greatly improved by conventional heavy cold rolling and a subsequent annealing process. The grain refinement strengthening acts as the primary factor. Different yield phenomena and microstructural evolution for tested steels are systematically analyzed. The change in initial free mobile dislocation density is the core cause of the preyield plateau phenomenon.